Integrated Models of a Gas Metal ARC Welding Process and Inverter based Power Supply for Process Control Simulation Studies - Golob, M. (Elektronika ir Elektrotechnika, 2014)
The objective in this paper was to combine the simulation of a Gas Metal Arc Welding (GMAW) process model with the simulation model of an inverter-based power machine. The GMAW process was considered as an electrical circuit and the mathematical model was based on physical descriptions of several parts of the GMAW process, as were the electric circuit of the power supply, the arc dynamics, and the electrode melting process. A simple welding application was simulated and the welding parameters were derived from several experimental conditions. Next, the dynamic behaviour of a full-bridge DC-DC converter was simulated and a suitable discrete PI controller proposed for welding current feedback control. Both models, the GMAW model and the inverter power supply model, were combined into a new simulation model of the GMAW process application together with an inverter based welding machine. DOI: http://dx.doi.org/10.5755/j01.eee.20.7.8016